(untitled) (Research, Society and Development, 2021)
This article aims to evaluate the preoperative use of gabapentin in the control of intra- and postoperative pain in patients with idiopathic bilateral carpal tunnel syndrome (CTS). A prospective, randomised, double-blind study involving 45 subjects with severe CTS, 23 receiving treatment (gabapentin 600 mg) and 22 receiving placebo (control), who underwent an open surgical approach in one hand under local anaesthesia. Information related to the patients’ profile, safety of the surgical procedure, history of pain, adverse effects, numbness, and medications used were collected during the 14 days of the procedure and evaluated by Generalised Estimated Equations and Generalised Linear Mixed Models. The treatment and control groups were homogeneous regarding the patients’ profile and surgical procedure data. The patients who used gabapentin 600 mg had a better evaluation during surgery (d = 0.655), anaesthesia (d = 0.854), and on the first night of sleep (d = 1.323), and they reported a higher degree of satisfaction with the surgery after 14 days (d = 1.091). The treatment group reported decreased pain in the operated hand in a 24-hour period (r = 0.34, 95% CI: 0.223–0.457) and in the 14-day follow-up period (r = 0.412, 95% CI: 0.217–0.608). These results were not impacted by the medications used and remained consistent over time. The use of a single dose of gabapentin 600 mg in the preoperative period proved to be safe and effective in reducing postoperative pain, and the improvement was noticed by the patient.